Mechanochemical destruction of tehnical Hexachlorocyclohexane with Calcium oxide - Pelitli, Volkan; Kurt, Ugur; Canli, Oltan (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2019)
In the present study, we investigate the mechanochemical destruction efficiency of technical hexachlorocyclohexane (t-HCH) by planetary ball milling with calcium oxide (CaO). After the mechanochemical reaction, t-HCH amount of the residue was measured by Gas chromatography coupled electron capture detector (GC-mu ECD) and found the destruction efficiency was 99,7% after 6 h milling. The intermediate products, such as pentachlorocyclohexene (PCCH), tetrachlorobenzene (TeCBz), trichlorobenzene (TriCBz), dichlorobenzene (DCBz) and monochlorobenzene (MCBz) were detected by Headspace Gas Chromatography Mass Spectrometry (GC-MS) and the main destruction pathway of t-HCH was proposed. The results showed us the final products were amorphous carbon and waster soluble chlorine. According to the results; mechanochemical process is a promising non-combustion technology that can be used for the destruction of t-HCH in the presence of CaO.
Keywords: Hexachlorocyclohexane; mechanochemical process; destruction; ball mill; DECHLORINATION; DECOMPOSITION; MECHANISM; Engineering